Influence of Piperine on Collagen Color and Degree of Conversion of a Universal Adhesive System Applied to Bleached Dentin (Global Journal of Medical Research, 2024)
Aims The aim was to evaluate the influence of piperine on the collagen staining and on the degree of conversion of the universal adhesive system applied to the bleached dentin Methods The piperine extraction process was carried out using a water reflux system and confirmed by UV-Vis spectrophotometry For collagen staining analysis dentin collagen disk were analyzed with a spectrophotometer Regarding the collagen color evaluation there was no statistically significant difference between the groups regarding L a b e E p 0 05
Keywords: tooth whitening antioxindant pipper nigrum